Diseño organizacional y gestión del talento humano para la empresa Avícola Serrano de la ciudad de Catamayo. - Castillo Ortega, Jorge Luis (2012)
Poultry ham is a private company domiciled in the canton Catamayo, province of Loja, whose main purpose is the breeding, fattening and marketing of chicken and balanced development of consumption, which aims to buy broiler newborns, and distributes in different sheds for farming and marketing. The following research work, intended to contribute in some way to improve talent management company Poultry Serrano, offering technical and administrative methods to help improve the performance of each of the activities developed by the staff of the same . After having analyzed the results based on research work found that the company "Poultry Serrano" lacks an organizational design and has not been established mission, vision, organizational charts and manuals of functions that enable the company to define its structural configuration. Another shortcoming of Poultry Serrano is not applying the techniques of admission of use of human talent, making the process of recruitment, selection, hiring, training and motivation in an empirical way. This situation can develop proposals focused on organizational design and talent management. That is why we propose the following: Structural functional organization charts and positional, to design the organizational structure of the company defining the degree of responsibility and authority of each job. Operating manuals which describe each of the activities to be undertaken by those in the workplace, detailing aspects such as roles, responsibilities and minimum requirements for the position. Recruitment techniques, selection, hiring the tools which constitute a great contribution to the efficient management of human talent, as well as plans for training and motivating employees. Similarly establishing the method of job evaluation points, which allows a salary adjustment based on working conditions and minimum requirements of each job salary compensation making a fair and equitable. Within the management of human talent is important to know the performance of each of the employees within the company, which is why it raises the graphic scale method which allows to know the development that has the personnel working in Poultry Serrano . All these aspects are focused on improving the management of human talent Serrano Poultry Company, which seeks to have the best talents to contribute their skills, abilities and skills to achieve organizational objectives raised.